The Influence of Capital Structure and Managerial Ownership on Company Performance Through Agency Cost as Intervening Variables - Yamasitha Yamasitha (Journal of Accounting and Finance Management, 2020)
The purpose of this research is to examine the effect of capytal structure and managerial ownership on firm performance by agency cost as an the intervening variable. The sample used is a manufacturing company sector 4 (varoius industries) and sector 5 (goods industries consumsy) listed in Indonesia Stock Exchange in 2015-2019. Were selected in the sampling method of sample use purposive.The data use dissecondary data and the analysis methodusedis multiple regression path analyze method. The results showed that the independent variables capital structure has a negative effect on the agency cost, and managerial ownership has a negative effect on the agency cost. The independent variables capital structure has a negative effect on the firm performance and capital structure has a negative indirect effect on the firm performance by agency cost. The independent variables managerial ownership has no positive effect on the firm performance and managerial ownership has a negative indirect effect on the firm performance by agency cost. Agency cost has no negative effect on the firm performance.